Evaluation of Contrast Sensitivity, Chromatic Vision, and Reading Ability in Patients with Primary Open Angle Glaucoma - Maria P. Bambo; Blanca Ferrandez; Noemi Güerri; Isabel Fuertes; Beatriz Cameo; Vicente Polo; Jose M. Larrosa; Elena Garcia-Martin (Journal of Ophthalmology)
Purpose. To compare contrast sensitivity, acquired color vision deficiency, and reading ability in patients with glaucoma at different stages of the disease and to establish correlations between visual field parameters and visual function scores. Methods. This prospective cross-sectional study included 121 glaucoma patients. Subjects with a diagnosis of chronic open angle glaucoma were recruited and classified according to Hodapp-Parrish-Anderson criteria. Patients with severe visual field defects were excluded because they were older, which could bias the interpretation of visual function tests. Contrast sensitivity was measured using the Pelli-Robson Chart and the CSV1000E test. Chromatic vision was evaluated using the Farnsworth-panel D15 and the L’Anthony D15 tests of Vision Color Recorder software. Reading ability was measured using Radner-Vissum test. Results. Contrast sensitivity (with photopic and mesopic luminance with glare) differed significantly between patients with early and moderate visual field defects (p<0.05). Reading ability scores and results of the chromatic vision tests did not differ significantly between the two groups. Significant and moderate Spearman correlations between visual field indexes and contrast sensitivity tests were detected. Conclusions. Contrast sensitivity was significantly worse in patients with moderate glaucoma compared to those with early-stage glaucoma. Evaluation of visual function in clinical practice provides important information to address a glaucoma patient’s vision complaints.